2021
DOI: 10.3390/ph14121264
|View full text |Cite
|
Sign up to set email alerts
|

Medical-Grade Honey Outperforms Conventional Treatments for Healing Cold Sores—A Clinical Study

Abstract: Cold sores are nasolabial blisters caused by herpes simplex virus (HSV) infections. Novel therapies demonstrating simultaneously antiviral activity and improved wound healing are warranted. The aim of this study was to investigate the efficacy of medical-grade honey (MGH) for treating HSV-induced cold sores. A crossover trial was performed in patients with recurrent cold sores (n = 29). The majority (65.6%) of these patients experience four or more episodes per year, thus forming a valid self-control group. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Several other clinical studies have shown that L-Mesitran promoted the healing of different types of (infected) wounds while diverse previous treatments failed, suggesting a superior activity, and reiterating its cost-efficacy [ 13 , 44 , 45 , 46 , 47 , 48 ]. According to a series of 10 cats with cutaneous contaminated wounds that were treated with L-Mesitran, regrowth of hair and minimal scarring were evident [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several other clinical studies have shown that L-Mesitran promoted the healing of different types of (infected) wounds while diverse previous treatments failed, suggesting a superior activity, and reiterating its cost-efficacy [ 13 , 44 , 45 , 46 , 47 , 48 ]. According to a series of 10 cats with cutaneous contaminated wounds that were treated with L-Mesitran, regrowth of hair and minimal scarring were evident [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 Recurrent herpes labialis may respond to a trademarked medical-grade honey formulation, L-Mesitranâ, decreased sore healing time, increased subjective healing score, and decreased pain and itching compared to conventional cold sore treatments such as oral and topical acyclovir. 24 In another clinical trial, with a 1 : 1 random assignment of 952 adult patients experiencing a herpes simplex labialis episode, there was no evidence of a difference between medical grade kanuka honey and 5% acyclovir topical treatments. 25 In a clinical trial of 100 children aged 2-8, the group receiving a combination of honey and oral acyclovir had significantly earlier disappearance of herpes simplex gingivostomatitis than those receiving acyclovir alone.…”
Section: Human Herpesvirus Types 1 Andmentioning
confidence: 97%
“…Herpes labialis is evident as vesicles in the nasolabial region caused by herpes simplex virus HSV‐1 or HSV‐2 infections 23 . Recurrent herpes labialis may respond to a trademarked medical‐grade honey formulation, L‐Mesitran®, decreased sore healing time, increased subjective healing score, and decreased pain and itching compared to conventional cold sore treatments such as oral and topical acyclovir 24 . In another clinical trial, with a 1 : 1 random assignment of 952 adult patients experiencing a herpes simplex labialis episode, there was no evidence of a difference between medical grade kanuka honey and 5% acyclovir topical treatments 25 .…”
Section: Human Herpesvirus Types 1 Andmentioning
confidence: 99%
“…The combination of these antimicrobial mechanisms makes MGH highly effective against a broad spectrum of pathogens, irrespective of their resistance profiles, including multi-resistant bacteria (e.g., methicillin-resistant Staphylococcus aureus (MRSA), vancomycinresistant enterococci (VRE), and Pseudomonas aeruginosa), fungi (e.g., Candida albicans, nonalbicans Candida species, and Candida auris), and viruses (e.g., Influenza A virus, human immunodeficiency virus (HIV), and herpes simplex virus, type 1 (HSV-1)) [29,30,[53][54][55].…”
Section: Mgh Exerts Broad-spectrum Antimicrobial Activity Relying On ...mentioning
confidence: 99%